Characteristics and outcomes of patients with EGFR-mutation positive non-small-cell lung cancer receiving gefitinib beyond radiological progression. (3rd July 2018) - Hosomi, Yukio; Tanai, Chiharu; Yoh, Kiyotaka; Goto, Yasushi; Sakai, Hiroshi; Kato, Terufumi; Kaburagi, Takayuki; Nishio, Makoto; Kim, Young Hak; Inoue, Akira; Hasegawa, Yoshinori; Isobe, Hiroshi; et al.
ABSTRACT: Background : This study aimed to analyze the characteristics and outcomes of patients suffering from non-small-cell lung cancer (NSCLC) with epidermal growth factor receptor mutations ( EGFR m+) receiving gefitinib who remained clinically stable following confirmation of progressive disease (PD) using Response Evaluation Criteria in Solid Tumors (RECIST) (R-PD) and identify those who benefited from tyrosine kinase inhibitor therapy beyond PD. Research design and methods : The clinical courses of patients with EGFR m+ advanced NSCLC who received first-line gefitinib were investigated. Clinical PD (C-PD) was defined as one or more of the following: (1) symptomatic PD, (2) worsening performance status resulting from PD, (3) threat to a major organ(s), or (4) unequivocal multiorgan PD. Results : Of 529 patients, 258 experienced R-PD without C-PD. Among 258 patients, 91 received gefitinib beyond R-PD. Females were more likely to receive gefitinib beyond R-PD and exhibit a longer time from R-PD to C-PD than males (median days, 175 vs. 79.5). Survival beyond R-PD tended to be longer for elderly patients who received gefitinib beyond PD than for those who did not (median days, 458 vs. 336), but this was not the case for non-elderly patients (median days, 481 vs. 487). Conclusions : Some patients may benefit from continuation of gefitinib beyond PD.